Uji Pengaruh Profitabilitas, Leverage, Media Exposure Terhadap Pengungkapan Emisi Karbon Dengan Pemoderasi - Florencia, Vania; Handoko, Jesica (Program Studi Akuntansi FPEB UPI, 2021)
This study aims to examine and analyze the effect of profitability, leverage, media exposure on the disclosure of emissions with environmental performance as a moderating variable. The type of data used is quantitative data in the form of annual reports and sustainability reports. The object of research is mining companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 period. Technical data analysis using multiple linear regression and Moderated Regression Analysis (MRA). The results showed that profitability did not have a significant effect on carbon emissions disclosure. The size of the profitability does not affect the company's carbon emissions disclosure. Leverage has a negative effect on disclosure of carbon emissions. Media exposure has a positive effect on disclosure of carbon emissions. Companies will increasingly carbon emissions disclosure through the media to get a positive response from the public. Environmental performance weakens the relationship between profitability and media exposure on carbon emissions disclosure, but strengthens the effect of leverage on carbon emissions disclosure.